Konsep Dakwah Moderat: Tinjauan Ummatan Wasathan dalam Al-Qur’an Surat Al-Baqarah:143 - Fitri Rahmawati (Universitas Darussalam Gontor, 2021)
Era of globalization is defined as the era of ‘diplomacy’. The era in which Muslims are required to be moderate (wasathiyah). Muslims as moderate people must be able to integrate two different dimensions; dimensions of 'theocentric' (hablun min Allah) and 'anthropocentris' (hablun min an-nas). These demands are not require of the times, but the demands of the Qur'an which must be realized. The meaning of wasathiyah should not be taken from the understanding of extremists who tend to prioritize uncompromising toughness (ifrâth), or the understanding of liberalists who often interpret religious teachings very loosely, freely, even almost leaving the line of religious truth (tafrîth). The meaning of Islam as a religion wasathiyah must be appropriated from the explanation of the ulama. This is not to trigger 'missunderstanding' and intolerance that damage the appearance of Islam itself. Understanding the correct meaning of wasathiyah is able to form a conscious attitude in moderate Islam in the correctness (ummatan wasathan), realizing world peace, without violence on behalf of group, race, ideology and even religion.